Marcas de hesitação na fala de crianças com autismo: construção de sentidos sob o paradigma textual-interativo - Santos, Katiane Silva (2019)
Looking for references from studies on the language phenomenon concerning Autistic Spectrum Disorder (ASD), we observed a scarce number of publications in the area, especially regarding hesitation, since, in the vast majority, discursive processing within this spectrum, is treated with a pathologizing look. Given this, the general objective of this research is to analyze, in the light of the textual-interactive perspective, hesitation marks in the construction of spoken texts produced, in concrete interlocution situations, by children with Autistic Spectrum Disorder. In line with Marcuschi (1999, p. 159), we adopted in this research the position that hesitation “is part of communicative competence in interactive contexts of an oral nature and not a dysfunction of the speaker”. These marks manifest themselves through different resources, since they have a cognitive function (KOCH, 2016) to gain more time for text planning and verbalization (seen here as a process of social interaction), in order to continue what is being said. As a hypothesis, we present the fact that although the texts produced in orality, in socio-communicative situations, by children with autism reveal discursive aspects such as hesitation, repetition and interruption, the construction of meaning is evident. Therefore, we tried to observe the way these children with ASD, in socio-cognitive-discursive activities, constructed spoken texts in the interaction with professionals involved in the communicative process. In order to realize this proposal, we built a corpus from the oral texts produced by these children, based on the observations made during our visits to the Sun Ray Integration Center (CIRAS); Based on a qualitative, interpretative and descriptive methodology, we observed 10 children attended at this Center, among which 5 were chosen with a diagnosis of ASD. We use as instruments direct observation, notes in the field diary, questionnaires and audio recording. The recordings were transcribed and analyzed according to the rules of the Rio de Janeiro Cultured Oral Urban Standard Project. To support this study, regarding autism, we rely on the Diagnostic and Statistical Manual of Mental Disorders (DSM), Orrú (2012; 2016), Klin (2006), Bosa (2006), among others; Regarding the textual-discursive studies we take as a foundation the analyticaldescriptive proposals in Text Linguistics from the contributions of Koch (2015; 2016), Jubran (2015; 2017), Lima and Santana (2016), Cavalcante (2017). ) and Marcuschi (2015a). The final results of our research confirm the fact that spoken texts, that is, produced orally, in discursive-interactive situations, by children with Autistic Spectrum Disorder, construct meanings, even with the recurrence of hesitation marks. One of the most interesting phenomena of human language and one of the most interfering in the construction of meanings and understanding of spoken texts.